A comment on "Constant deceleration approach for the penetration analysis of rigid projectiles into concrete targets: Revisited" by D.Z. Yankelevsky and V.R. Feldgun, Int. J. Prot. Struct., pp. 1–18 (2020). Issue 3 (September 2020) - Rosenberg, Zvi; Dekel, Erez; Kositski, Roman
The purpose of this Comment is to highlight several inaccuracies in the recently published paper of Yankelevsky and Feldgun, which criticizes our work on concrete penetration. The main subject of their criticism concerns our treatment of the entrance phase in concrete penetration, and we show here that their claims are inaccurate and misleading. We do not engage in the existing debates concerning different approaches to the penetration mechanics of rigid projectiles.